Hubungan Antara Panjang Lengan, Kekuatan Otot Lengan Dan Daya Ledak Otot Lengan Dengan Kemampuan Chest Pass Pada Pemain Bola Basket Putra Di Smpn 4 Kota Malang - Andi S, Abdilla Dimas; Nurrochmah, Siti (Jurnal Porkes, 2025)
This study focuses on examining and determining the possibility of a relationship between arm length, arm muscle strength and arm muscle explosiveness with chest pass ability owned by male basketball players at SMPN 4 Malang City. The method used is descriptive explanatory. The population in the study amounted to 60 male basketball players at SMPN 4 Malang City. The technique used is stratified purposive systematic proportional random sampling with a portion of 90% of 60 players so that the sample in this study amounted to 54 basketball players. The analysis technique used is parametric inferential statistics in the form of multiple correlations complemented by multiple regression analysis. The results of the multiple correlation test research obtained a coefficient = 0.752 and Sig.p = 0.000 < α = 0.05. The chest pass skill is 56.6% of each independent variable: variable arm length 21.33%; arm muscle strength 15.08%; arm muscle explosive power 20.23%. The final results of this study indicate that the ability to perform chest passes in basketball games has a positive and linear relationship with a combination of three physical condition factors namely arm length, arm muscle strength, and arm muscle explosiveness when analyzed simultaneously.